Do Attributes of the Board of Commissioners Affect Accounting Conservatism? The Role of Foreign Institutional Investors - Sari, Maria Puspita Nugrahaning; Setiawan, Doddy (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 1 (2024)DO - 10.24843/JIAB.2024.v19.i01.p12, 2024)
This study examines the influence of board of commissioners' characteristics on accounting conservatism, with foreign institutional investors serving as a moderating variable. One novel aspect of this research is the focus on the tenure of the president commissioner. The methodology employed is quantitative, utilizing a panel data regression model via EViews. Data analysis was conducted using the Fixed Effect Model (FEM) test. The sample includes 314 manufacturing companies listed on the IDX from 2019 to 2022. The findings reveal that the tenure of the president commissioner, alongside the presence of independent and female commissioners, significantly impacts the application of accounting conservatism. Foreign institutional investors moderate the effect of the president commissioner's tenure on accounting conservatism but do not influence the relationship between the presence of independent and female commissioners and the application of accounting conservatism. Keywords:  board of commissioners, accounting conservatism, foreign institutional investors